Analisis Kebijakan Pembelajaran Jarak Jauh pada Pelajaran Bahasa Indonesia di Masa Wabah Virus Corona - Triyanto (Diglosia: Jurnal Kajian Bahasa, Sastra, dan Pengajarannya, 2020)
This research aims to explore and describe a policy made by the government, specifically the policy related to distance learning during the Corona virus epidemic. The research method used is qualitative with a case study approach. Data collected were interviews with school principals, Indonesian language teachers, and observations in five classes, as well as distributing questionnaires with school principals, homeroom teachers, Indonesian language teachers, student guardians, and the students. Interview data were analyzed using "within case and cross-case analysis" between informants. The data obtained is processed into a database and made in the form of files to facilitate data processing. The results showed that SMP Muhammadiyah 1 Prambanan has implemented most of the distance learning policies instructed by the government through SE No. 4 of 2020. The learning responsibilities given to students are not burdensome in terms of materials, facilities, and infrastructures. The learning taught includes life skills during corona virus epidemic. The learning methods and the learning process are implemented in accordance with students' conditions. The feedback given by the teacher is still in the form of points and not in accordance with government instructions. The Indonesian language learning is carried out in accordance with government instructions.